Implementasi Line Balancing Untuk Meningkatkan Output Produksi Lini Assembly Loading Biscuit Di Industri Keramik Tangerang - Hartono Hartono; Andriyansyah Andriyansyah (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
Advances in industrial technologies are growing rapidly, the Company is trying to make periodic improvements to maintain its competitiveness by selecting the correct working method, the Tangerang ceramic industry is an industry engaged in the manufacture of porcelain, in January-December 2021 the production output never reaches the given standard company. The purpose of this research is to find out the cause of the non-achievement of the production target in January-December 2021, find the root of the problem and provide improvements to the non-achievement of the production target. The method used in this study is Line Balancing to calculate the line efficiency value of the Tangerang ceramic industry and find bottleneck stations that result in not achieving production targets, in this study fishbone diagrams and 5why are also used as additional tools to find the root of the existing problems. The results of this study indicate that the production value on the biscuit loading assembly line is 77.56% with a bottleneck at the finishing station with a cycle time of 32.82sec, or a standard time of 36.102 sec exceeding the standard takt time given to achieve the target of 1,800 pcs/shift by Therefore, improvements were made by increasing the number of special finishing operators, replacing raw materials with better quality, re-setting the machine or upgrading some spare parts, every item to be dismantled has been prepared near decha. From the results of the improvement in production output from January to March 2022, it increased by 84.83%.Â Keywords: Line Balancing, Porcelain, Bottle Neck, Fishbone Diagram, 5 Why,Â Line Efficiency, Calculation of Standard Time.